Leaf blade anatomy characteristics of the genus Amorphophallus Blume ex Decne. in Thailand - Sookchaloem, Duangchai; Sungkajanttranon, Oraphan; Petchsri, Sahanat; Horadee, Suchai; Huayhongthong, Chaiya; Vanapanich, Amphon; Wongsawaddiwattana, Chanu (Agriculture and Natural Resources, 2016)
Twenty-three species of Amorphophallus Blume ex Decne. were collected from several areas of Thailand between November 2008 and May 2012, and grown under greenhouse conditions with 70% sunlight. Leaf blade anatomy characteristics were studied using free hand section and epidermal peeled slides before being observed using a light transmission microscope from May 2011 to November 2013. The results showed the different anatomical characteristics of each species. The midribs in cross section were curved, or had 5, 6, 7, 8 or 12 lobes. Vascular bundles numbered 5, 6, 7, 8, 9, 10, 13, 15, 16 or 23. The upper and lower epidermal cell walls had three subtypes-straight-sided, undulate or sinuous anticlinal. Both sides of the epidermal cell wall can be similar or can vary in each species. There were 1, 2, 3, 4 or 6 subsidiary cells along both sides of paired guard cells and the stomatal type was paracytic and stomatal subtypes varied from species to species, being brachyparacytic, hemiparacytic, amphibrachyparacytic, paratetracytic or parahexacytic. The stomatal number was 16-104/mm2 of leaf area and varied with the leaf gloss and leaf texture of each species.